Necessity of Dairy Farming in Gairsain Area of Garhwal Himalayas - Chanyal, Sheetal; Sharma, Nidhi; Srivastava, R. K.; Chhimwal, Monika (International Journal of Livestock Research, 2019)
India is the leading milk producing country in the world, which produces around 176 million tonnes milk per year with small-scale producers as its backbone. At present, dairy is one of the fastest growing enterprises in the booming economy of the country. Livestock development is one of the top priorities in the development agenda of newly created Uttarakhand State with dairying as one of the important dimensions. During present study, it was observed that no organized dairy cooperative is working in the study area Gairsain and consumers have also suffered from low consumption. The coverage extends to the economics, breeding, nutrition, lactation, management and marketing of dairy cattle and milk production. The study revealed that majority of dairy farmers had medium level of knowledge on different components of scientific dairy farming practices. Farmers in the study area were completely dependent on the locally available bio-resources like oak tree leaves and different species of wildly grown grasses in the forest area for feeding the animals round the year. In Gairsain major milk producing livestock include cow (45%), buffaloes (21%) and goats (28%). It was observed that there is a necessity of dairy development for income generation; moreover, alternate milk producing animal like goat has also been proposed for income increment of the farmers. They have majority of animals with low productivity due to inadequate nutrition, less feeds and fodder, which could not be used for income generation activity. In the study area, people are forced to buy different brands of dairy products with high price, as there is no alternate source. It was analyzed that the inefficiencies existed in milk production, procurement pattern and marketing in that area are few reasons why products are sold at high price. It was also analyzed that sellers of study area used dairy products of different brands, leading to earning of huge revenue through local people. Therefore, the present study tries to propose a model for eliminating these complications by proposing livestock and dairy farming in Gairsain, which will also act as a major source of livelihood to millions of marginal and small dairy farmers throughout the state. Dairy producers should be educated for scientific practices, feeds and nutrient of animal, regular trainings and linking producers with dairy cooperative federation for regular marketing.